The Effectiveness of the Jember Regent’s Circular Letter Number 474/196/35.09.317/2024 on Marriage Dispensation Application Services as an Effort to Prevent Child Marriage in Silo District - Misbahul Ikhsan; Beni Ashari (al-Afkar, Journal For Islamic Studies, 2026)
The existence of Circular Letter (SE) of the Regent of Jember No. 474/196/35.09.317/2024 concerning the service for marriage dispensation applications is formulated as a strategic response to the high number of such applications an the absence of regional regulations, while also examining the effectiveness of its implementation in the Silo District. This study employs a field research method with a juridical-empirical approach, with data collected through interviews, obsevations and document studies. The findings reveal that the implementation of this Cilcular Letter has transformed the procedure for marriage dispensation applications into a multi-layered bureaucracy requiring cross-sectoral recommendations, including medical, psychological, and premarital educational aspects. Quantitatively, this administrative tightening has proven successful in significantly reducing the number of applications submitted to official authorities. However, the analysis also uncovers a sociological paradox, the high costs an procedural complexity have driven the community in Silo District to exploit legal loopholes by resorting to unregistered (sirri) marriages. This resistance is rooted in strong local traditions and limited legal literacy among the community. In conclusion, while the tightening policy is administratively effective in filtering applications, it has not yet addressed the core cultural issues. Therefore, a harmonization between bureauctratic regulatory enforcement and socio-cultural educational approaches is required to significantly break the chain of child marriage.